Hyperamylinemia as a risk factor for accelerated cognitive decline in diabetes. (2nd November 2015) - Ly, Han; Despa, Florin
Abstract : Type II diabetes increases the risk for cognitive decline via multiple traits. Amylin is a pancreatic hormone that has amyloidogenic and cytotoxic properties similar to the amyloid-β peptide. The amylin hormone is overexpressed in individuals with pre-diabetic insulin resistance or obesity leading to amylin oligomerization and deposition in pancreatic islets. Amylin oligomerization was implicated in the apoptosis of the insulin-producing β-cells. Recent studies showed that brain tissue from diabetic patients with cerebrovascular dementia or Alzheimer's disease contains significant deposits of oligomerized amylin. It has also been reported that the brain amylin deposition reduced exploratory drive, recognition memory and vestibulomotor function in a rat model that overexpresses human amylin in the pancreas. These novel findings are reviewed here and the hypothesis that type II diabetes is linked with cognitive decline by amylin accumulation in the brain is proposed. Deciphering the impact of hyperamylinemia on the brain is critical for both etiology and treatment of dementia.